2019
DOI: 10.1080/15384101.2019.1578145
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin accessibility changes are associated with enhanced growth and liver metastasis capacity of acid-adapted colorectal cancer cells

Abstract: Song He (2019) Chromatin accessibility changes are associated with enhanced growth and liver metastasis capacity of acid-adapted colorectal cancer cells, Cell Cycle, 18:4, 511-522, ABSTRACTThe acidic extracellular microenvironment, namely acidosis, is a biochemical hallmark of solid tumors. However, the tumorigenicity, metastatic potential, gene expression profile and chromatin accessibility of acidosis-adapted colorectal cancer cells remain unknown. The colorectal cancer cell SW620 was cultured in acidic medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 33 publications
(40 reference statements)
1
17
0
Order By: Relevance
“…SMAD8) showed correlation with good OS in four types of cancer (pancreatic, lung, colon and glioblastoma; Figure 3 C, Table 1 ). SMAD9, a receptor-SMAD activated by Bone Morphogenetic Protein (BMP) receptors, was also upregulated by acidosis in colon cancer cells [ 45 ]. Although the link of high expression to better OS makes SMAD9 upregulation an unlikely driver of acidosis-induced pro-tumorigenic effects, activating SMAD9 mutations were linked to some gastric cancers [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…SMAD8) showed correlation with good OS in four types of cancer (pancreatic, lung, colon and glioblastoma; Figure 3 C, Table 1 ). SMAD9, a receptor-SMAD activated by Bone Morphogenetic Protein (BMP) receptors, was also upregulated by acidosis in colon cancer cells [ 45 ]. Although the link of high expression to better OS makes SMAD9 upregulation an unlikely driver of acidosis-induced pro-tumorigenic effects, activating SMAD9 mutations were linked to some gastric cancers [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another study demonstrated that THAP9 antisense RNA 1 promoted the progression of PC via sponging miR-484 and interacting with Yes-associated protein 20 . Zhou et al showed the aberrant expression of paired mRNA/lncRNA in acidosis-adapted colorectal cancer cells, indicating that deregulated lncRNA might be involved in the acidosis adaption-enhanced growth and metastasis of colorectal cancer cells 21 . Another study showed that acidosis-induced ribosomal intergenic spacer lncRNA operated as a molecular switch of regulating the structure and function of the nucleolus 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Patients with higher PD-1/PD-L1 signal represents an immune-inhibited status (19,25) Chromatin accessibility reflects both aggregate TF binding and the regulatory potential of a genetic locus (11). Chromatin accessibility changes are associated with tumor initiation, migration, tumor metastatic progression (12,26,27). ATACseq has emerged as one of the most widely used methods for accessing genome-wide chromatin accessibility.…”
Section: Discussionmentioning
confidence: 99%